Human dental enamel and dentin structural effects after Er:yag laser irradiation - Lima, Darlon Martins; Tonetto, Mateus Rodrigues [UNESP]; Mendonça, Adriano Augusto Melo de; Elossais, André Afif [UNESP]; Saad, José Roberto Cury [UNESP]; Andrade, Marcelo Ferrarezi de [UNESP]; Pinto, Shelon Cristina Souza; Bandéca, Matheus Coelho (Jaypee Brothers Medical Publishing, 2014)
Ideally projected to be applied on soft tissues, infrared lasers were improved by restorative dentistry to be used in hard dental tissues cavity preparations-namely enamel and dentin. This paper evidentiates the relevant aspects of infrared Erbium laser's action mechanism and its effects, and characterizes the different effects deriving from the laser's beams emission. The criteria for use and selection of optimal parameters for the correct application of laser systems and infuence of supporting factors on the process, such as water amount and its presence in the ablation process, protection exerted by the plasma shielding and structural factors, which are indispensable in dental tissues cavity preparation related to restorative technique, are subordinated to optical modifcations caused by the interaction of the energy dissipated by these laser light emission systems in the targeted tissue substrate. Clinical relevance: Differences in the action of infrared Erbium laser system in regard to the nature of the ablation process and variations on the morphological aspects observed in the super-fcial structure of the target tissue irradiated, may be correlated to the structural optical modifcations of the substrate produced by an interaction of the energy propagated by laser systems.
Keywords: Laser ablation; Dental enamel; Human dentin